IMF Staff papers : Volume 35 No. 1. (IMF Staff Papers; IMF Staff Papers, 1988)
A central proposition regarding effects of different mechanisms of fi-nancing public expenditures is that, under specific circumstances, it makes no difference to the level of aggregate demand if the government finances its outlays by debt or taxation. This so-called Ricardian equivalence states that, for a given expenditure path, substitution of debt for taxes does not affect private sector wealth and consumption. This paper provides a model illustrating the implications of Ricardian equivalence, surveys the litera-ture, considers effects of relaxing the basic assumptions, provides a frame-work to study implications of various extensions, and critically reviews recent empirical work on Ricardian equivalence.